Efektivitas Pelatihan Pengukuran Antropometri Terhadap Perubahan Pengetahuan Pengetahuan dan Keterampilan Kader Posyandu Wilayah Puskesmas Nelle - Mariyani, Ketut; Suarjana, I Made; Agustini, Ni Putu (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
The knowledge and skills of Posyandu cadres in anthropometric measurements are very important, because they will affect the quality of the data produced. This study aims to determine the effectiveness of training on changes in the knowledge and skills of Posyandu cadres in anthropometric measurements carried out using the Quasi-experimental method involving 31 samples in the Nelle Health Center area, Sikka Regency. The training materials include toddler anthropometric parameters and measurement steps. The results of this study showed that the average knowledge before training was 74.4 after training 90.3 and the Wilcoxon test results were 0.000 Asymp.Sig (2-talled). The average skills before training were 51.7 after training 85.0 and the Wilcoxon test results were 0.000 Asymp.Sig (2-talled). On the one hand, the knowledge and skills of the cadres are still lacking. Cadres do not understand the name and function of the tools and the basic principles of measurement, especially in measuring the length infants. Errors also occur during weighing, where the Unit Hold button is not pressed so that the results are not locked. In addition, the measurement of toddler height has not ensured the body position according to the five reference points on the measuring instrument. The measurement LILA is also not accurate because the determination of the midpoint of the arm has not been done correctly. The results of the analysis showed that there were changes in the knowledge and skills of cadres after training. Anthropometric training is quite effective in improving the knowledge and skills of cadres.